2020
DOI: 10.1111/1745-9125.12257
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing inequality in the courts: Decomposing racial and ethnic disparities in detention, conviction, and sentencing*

Abstract: A significant body of literature has examined racial and ethnic inequalities in sentencing, focusing on how individual court actors make decisions, but fewer scholars have examined whether disparities are institutionalized through legal case factors. After finding racial and ethnic inequalities in pretrial detention, conviction, and incarceration based on 4 years of felony court data (N = 83,924) from Miami‐Dade County, we estimate nonlinear decomposition models to examine how much of the inequalities are expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 98 publications
(214 reference statements)
1
33
1
Order By: Relevance
“…Any understanding of individual sources of racial bias, however, cannot be divorced from a broader appreciation of the structural influences that also shape and constrain punishment. Recent work has suggested that broader, macro-level factors may be especially important for understanding overarching patterns of racial inequality in the justice system (Bushway & Forst, 2013;Omori & Petersen, 2020). Some classical scholarship has portrayed organizations as bureaucratically rational and race neutral (Weber, 1978), but more recent work has argued race and ethnicity play fundamental roles in the structuring of organizational outcomes (Bonilla-Silva, 1997).…”
Section: Individual and Structural Perspectives On Inequality In Punishmentmentioning
confidence: 99%
“…Any understanding of individual sources of racial bias, however, cannot be divorced from a broader appreciation of the structural influences that also shape and constrain punishment. Recent work has suggested that broader, macro-level factors may be especially important for understanding overarching patterns of racial inequality in the justice system (Bushway & Forst, 2013;Omori & Petersen, 2020). Some classical scholarship has portrayed organizations as bureaucratically rational and race neutral (Weber, 1978), but more recent work has argued race and ethnicity play fundamental roles in the structuring of organizational outcomes (Bonilla-Silva, 1997).…”
Section: Individual and Structural Perspectives On Inequality In Punishmentmentioning
confidence: 99%
“…The role of prior punishments in cumulative disadvantage is important when considering that disadvantage may disproportionately accumulate for some individuals through the intersection of legal factors (e.g., prior punishments) and extra‐legal factors (e.g., race)—particularly when “status‐linked attributions and stereotypes” influence opinions on dangerousness or blameworthiness [see Ulmer (2012) for a theoretical review]. Although older sentencing research concluded that racial disparities are diminished when legal factors are controlled (Baumer, 2013; Spohn, 2000; Ulmer, 2012; Zatz, 2000), recent decomposition studies have shown that racial disparity stems from those differences in prior legal factors (e.g., Donnelly & MacDonald, 2018; Omori & Petersen, 2020). This work has suggested that disparities build primarily through differential impact (i.e., Blacks have longer criminal record than Whites) rather than differential treatment (i.e., Blacks with same record as Whites are treated more harshly; Hamilton, 2015; Schlesinger, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This work has suggested that disparities build primarily through differential impact (i.e., Blacks have longer criminal record than Whites) rather than differential treatment (i.e., Blacks with same record as Whites are treated more harshly; Hamilton, 2015; Schlesinger, 2011). The process by which prior records are built “institutionalizes” inequality (Omori & Peterson, 2020). What is less well understood is if racial disparities persist in a sentencing guidelines setting after controlling for the formal impact of prior record in the guidelines scoring.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations